Pengembangan Model Diklat Interaksi dan Komunikasi Anak dengan Autisme - Trisno Ikhwanudin (Universitas Sarjanawiyata Tamansiswa, 2017)
This research is motivated by the need for the design and implementation of training model for the development of interaction and communication of children with autism that is effective according to the needs of the institution and the field. The formulation of the problem is